SUBSTITUTION COMPONENT CULTIVATION MEDIA OF PHOTO-FERMENTATION PROCESS FOR LOW COST HYDROGEN GAS BIOPRODUCTION - Susilaningsih, Dwi -; Uhtiza, Tami Astie; Anam, Khairul - (LIPI Press, 2017)
Employing the Rhodobium marinum bacteria as an agent of hydrogen bioproduction with facultative fermentation condition needs two steps of cultivations, i.e., pre-culture and hydrogen production periods with different media. The two steps cultivation is important state for hydrogen gas production rate. ASY (Ammonium, Succinate, and Yeast extract) is usually used as standard medium in biohydrogen production and mostly the component is analytical grade of chemicals. Series of cultivation media substitution by combining ASY with other cost-effective chemicals were investigated. The total of sixteen combinations of media were observed (P0-P15). Cultivation condition of R. marinum was set in an illuminated light of 31.17 µmol s-1m-2photon and agitated in shaker of 120 rpm for nine days. The experiment was designed as random selection with anova analyses. The results exhibited that P7 medium combination released the highest hydrogen gas of 61.29±0.52 ml/80 ml media among the others combination media. Using one-way ANOVA, there was a statistically significant difference between the mean number and condition and it was found P7 was significantly different with the others combination media, except P7 was insignificantly different with P3 only. Overall, the combination media is cheaper than the ASY medium. The ASY medium price is about USD 677, and the substitution media prices were ranging from USD 4.24 to USD 613.47. However, the further research on optimisation cultivation condition is needed.